Novel mesoporous FeAl bimetal oxides for As(III) removal: Performance and mechanism. (February 2017) - Ding, Zecong; Fu, Fenglian; Cheng, Zihang; Lu, Jianwei; Tang, Bing
Abstract: In this study, novel mesoporous FeAl bimetal oxides were successfully synthesized, characterized, and employed for As(III) removal. Batch experiments were conducted to investigate the effects of Fe/Al molar ratio, dosage, and initial solution pH values on As(III) removal. The results showed that the FeAl bimetal oxide with Fe/Al molar ratio 4:1 (shorten as FeAl-4) can quickly remove As(III) from aqueous solution in a wide pH range. The FeAl-4 before and after reaction with As(III) was characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), transmission electron microscopy (TEM), high-resolution transmission electron microscopy (HR-TEM) and selected area electron diffraction (SAED), Brunauer–Emmett–Teller (BET) surface area measurement, and X-ray photoelectron spectroscopy (XPS). The BET results showed that the original FeAl-4 with a high surface area of 223.9 m 2 /g was a mesoporous material. XPS analysis indicated that the surface of FeAl-4 possessed a high concentration of M-OH (where M represents Fe and Al), which was beneficial to the immobility of As(III). The excellent performance of FeAl-4 makes it a potentially attractive material for As(III) removal from aqueous solution. Graphical abstract: Highlights: Novel mesoporous FeAl bimetal oxides with large surface area were synthesized. FeAl bimetal oxides performed much better than their single metal oxides. Over 99% of As(III) was removed in 90 min at pH 3.0–11.0 by FeAl bimetal oxides. As(III) was removed by its complexation with surface OH of FeAl bimetal oxides.